Le Roman de Perceforest, la Sicambre et la guerre de Cent Ans - Levente Selaf (Revue des Langues Romanes)
The article is dedicated to the analysis of the meaning of two episodes of the novel opposing the king of Sicambre to two Breton knights, who, in turn, manage to deprive him, the one of his fiancée, the other of his wife. This offense will be avenged by a nephew of the king and will result in the conquest of Britain by the Sicambrins and their allies, and the rise to the throne of England of a dynasty from both nations. The appearance of Sicambre provides a special intertext for this essentially Breton novel. It is a mythical city, invented by the Historia regum francorum, place of residence for several centuries of Trojan refugees who will become the ancestors of the French. The analysis proves that, by this reference, England and France oppose each other in the distant past: the ancestral conflict prefigures the Hundred Years' War. This explains the confused location of this country: in part symbolic (by its identification with Nubia), in part traditional (close to the Danube) and in part functional, to suit the rather limited geographical setting of the novel (close to the "North Sea"). By interpreting this motif we can also confirm the date of the novel from the first half of the 14th century (by pushing the date ante quem until 1350).